Splenektomie transdiafragmaticky - Chudáček, Josef; Klos, Dušan; Gregořík, Michal (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2023)
The spleen is one of the most commonly injured organ in blunt traumas to the chest and abdomen. Splenic injury can be a serious complication of fracture of the left 9th to 11th rib. The authors present a case report of a 65-year-old male patient with a blunt trauma to the left chest and abdomen, diagnosed with multiple left rib fractures, left hemothorax and splenic injury with a small subcapsular hematoma with no signs of active splenic bleeding. Due to hemodynamic instability and a large volume of blood loss via the chest drain, the patient was indicated for emergency left thoracotomy. A perforation in the lower lobe of the left lung caused by rib fractures was found, which was treated with sutures. Furthermore, the diaphragm was examined, two ruptures were identified from which blood was coming out, and thus a phrenotomy was performed. The bleeding central splenic rupture came as a big surprise. A spleen preserving surgery was impossible, therefore a splenectomy had to be performed, followed by chest wall stabilization with splints. Transthoracic approach to manage the splenic injury through phrenotomy should not be used as a standard. In a selected group of patients with concomitant chest and upper abdominal organ injuries, the use of this surgical approach appears to be highly beneficial. Key words: splenic injury, splenectomy, thoracotomy, rib fractures, diaphragmatic rupture.
Keywords: Abdominal Injuries; hematom; Splenectomy; lidé; poranění břicha; splenektomie; Humans; Aged; fraktury žeber; senioři; Male; mužské pohlaví; Rib Fractures; Hematoma